2012
DOI: 10.1007/s10640-012-9585-z
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity, Pulse Fishing and Endogenous Lifespan in Beverton-Holt Models

Abstract: Optimal management in a multi-cohort Beverton-Holt model with any number of age classes and imperfect selectivity is equivalent to finding the optimal fish lifespan by chosen fallow cycles. Optimal policy differs in two main ways from the optimal lifespan rule with perfect selectivity. First, weight gain is valued in terms of the whole population structure. Second, the cost of waiting is the interest rate adjusted for the increase in the pulse length. This point is especially relevant for assessing the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Da Rocha & Gutiérrez, 2011;Da-Rocha & Pujolas, 2011;Da Rocha & Mato-Amboage, 2016;Da Rocha & Sempere, 2016;Da Rocha, Cerviño, & Gutiérrez, 2010;Da Rocha, Gutiérrez, Cerviño, & Antelo, 2012;Da Rocha, Gutiérrez, & Antelo, 2013;Da Rocha, Gutiérrez, Garcia-Cutrin, & Jardim, 2015;Da Rocha, Gutiérrez, Garcia-Cutrin, & Touza, 2016;Da Rocha, Gutiérrez, Garcia-Cutrin, & Jardim, 2017;Arnason, 2002;Weninger and Just, 2002;Heaps, 2003;Weninger and Waters, 2003;Weninger, 2008;Kitts et al, 2011. 11 DISPLACE Bastardie, Nielsen, Andersen, & Eigaard, 2010Bastardie et al, 2013Bastardie et al, , 2014Bastardie, Nielsen, Eigaard, et al, 2015;Bastardie, Nielsen, Eero, Fuga, & Rindorf, 2017;Nielsen, Kristensen, Lewy, & Bastardie, 2014;www.…”
Section: Stoch Hcr (Itq Wealth)mentioning
confidence: 99%
“…Da Rocha & Gutiérrez, 2011;Da-Rocha & Pujolas, 2011;Da Rocha & Mato-Amboage, 2016;Da Rocha & Sempere, 2016;Da Rocha, Cerviño, & Gutiérrez, 2010;Da Rocha, Gutiérrez, Cerviño, & Antelo, 2012;Da Rocha, Gutiérrez, & Antelo, 2013;Da Rocha, Gutiérrez, Garcia-Cutrin, & Jardim, 2015;Da Rocha, Gutiérrez, Garcia-Cutrin, & Touza, 2016;Da Rocha, Gutiérrez, Garcia-Cutrin, & Jardim, 2017;Arnason, 2002;Weninger and Just, 2002;Heaps, 2003;Weninger and Waters, 2003;Weninger, 2008;Kitts et al, 2011. 11 DISPLACE Bastardie, Nielsen, Andersen, & Eigaard, 2010Bastardie et al, 2013Bastardie et al, , 2014Bastardie, Nielsen, Eigaard, et al, 2015;Bastardie, Nielsen, Eero, Fuga, & Rindorf, 2017;Nielsen, Kristensen, Lewy, & Bastardie, 2014;www.…”
Section: Stoch Hcr (Itq Wealth)mentioning
confidence: 99%
“…For age-structured models, Da Rocha et al (2012c) show numerically that pulses are not longer a viable optimal solution by maximizing the logarithm of the catches instead of just the catches. This result is reinforced in Da Rocha et al (2013) where it is shown analytically that the concavity properties of the management objective function are essential to remove optimal pulse fishing under imperfect selectivity. In the context of schooling fisheries, Tavhonen et al (2013) also show that using nonlinear harvesting costs that guarantee the concavity of the manager's objective function generates smooth optimal paths toward the steady state.…”
Section: Introductionmentioning
confidence: 95%
“…As mentioned in the introduction, while there have been some advances in the introduction of biological structure in bioeconomic models ( [33], [15]), there is still much need for further understanding about the implications of using biomass-based models in age structured populations. The aim of this section is to evaluate the impact of applying a heuristic harvesting control rule to a structured population.…”
Section: Stochastic Properties Of Heuristic Hcrmentioning
confidence: 99%
“…Target Points and Yield: Setting all periods F = F max it can be the case that we are not maximizing the yield ( [15]). In particular, Da Rocha et al [15] show that F max is not the optimal solution to maximization problem whenever the following inequality holds…”
Section: Hcr Reference Points and Riskmentioning
confidence: 99%